Personal professional development as a premise for teacher’s leadership - Remigijus Bubnys; Natalija Kauneckienė (Social Welfare: Interdisciplinary Approach, 2017)
Strategic documents on education emphasize learning leadership, discuss teachers’ activities related to continuous personal improvement in professional activities: by involvement in improvement of school activities, conducting research, participating in specialized group activities, projects, collaboration with colleagues, etc. Innovative trends of teachers’ professional development are the basis for the development of efficient leadership: a challenge promoting to introduce changes in teachers’ improvement by creating new conditions and possibilities for both teachers and school leaders. It is important for school leaders to ensure coherence between personal and institutional development needs, to create flexible structures while organizing support for teachers and promoting fostering of continuous learning culture in the organization. The research aim is to analyze experiences of heads of departments with regard to teachers’ personal professional development possibilities in their professional activities. The results disclose that teachers ambiguously assess the activity of the head of the department: concrete, individual support, attention, encouragement are emphasised but teachers are against observation and assessment of their activities. This is related to several reasons: teachers’ attitude towards change processes, innovations in teachers’ professional development, competencies of heads of education departments, and general school culture. It is important to create conditions for manifestation of teacher leadership in schools, creating conditions for every teacher to continuously improve the educational process, develop personal competencies, actively and responsibly participate in group activities, get involved in school improvement processes. Middle level leaders, heads of departments, acting as mediators while implementing individual, group and organizational level tasks, promote the development of teachers’ competencies.